The Financial Performance of Non-Urban Passenger Rail Services - Amos, Paul; Bullock, Richard (World Bank, Washington, DC, 2014)
The paper has three parts. It first summarizes the main factors that influence the costs and fare box cost recovery of rail passenger services, with illustrations from a range of different countries in which the Bank is involved in rail passenger operations. Second, it provides a generalized passenger service costing model, including indicative sets of input unit costs representing different levels of efficiency: this model is used for illustrative purposes in this paper but the structure can be readily applied by transport planners and policy-makers, with use of local parameters, in developing and transition countries. Third, it illustrates the cost drivers of services and the sensitivity of costs to different market and operational drivers. This report also addresses the sensitivity of cost to changes in key scenario assumptions. This shows that operating costs are minimized (but revenue not necessarily maximized) when operating speed is around 80 km/h. Above that speed, above-rail unit costs gradually increase as continuing reductions in time-related costs, principally rolling stock capital cost, are progressively offset by increased fuel consumption and equipment maintenance. Infrastructure maintenance costs also increase significantly with speed because of the need for higher quality track.